Developmental and molecular effects of pure-tone sine wave exposure on early zebrafish embryo development: Implications for reproductive health - Yan Zuo; Zhilan Bai; Kaixuan Yang; Ziyuan Lin; Xiaolin Hu; Huaqin Sun (Ecotoxicology and Environmental Safety)
Noise pollution has become a significant concern for human health, yet its effects on early embryonic development remain underexplored. Specifically, data on the impact of sine wave noise on newly fertilized embryos is limited. This study aimed to address this gap by using zebrafish embryos at the 1-cell stage as a model to assess the toxicity of sine waves, following OECD Test No. 236. We exposed embryos to sound levels of 90 decibels (dB) and above, observing increased deformity rates, delayed development, and reductions in body length, heart rate and brain size. To elucidate the molecular mechanisms underlying these effects, we employed transcriptomics, metabolomics, and epigenomics (m6A-MeRIP-seq). KEGG enrichment analysis revealed significant alterations in arachidonic acid metabolism, axon guidance, and ubiquitin-mediated proteolysis. In conclusion, our findings demonstrate that high levels of sine wave noise adversely affect early embryo development. These results provide crucial insights for developing strategies to mitigate noise pollution and protect early developmental stages.